Synthesis Of Polycrystalline Silicon Carbide Using Aluminum Carbide And Calcium Carbide With Silicon Tetrachloride - Ruzlan, Muhammad Hakim (Universiti Sains Malaysia, 2018)
In this research, the synthesis of high purity polycrystalline silicon carbide (SiC) at low temperatures of 400, 500 and 600 °C was investigated, and its efficiency in formation of SiC used in radiation dosimetry system which is main concerns nowadays and was investigated. The synthesis of SiC was initiated from raw material of aluminium carbide (Al4C3), Calcium Carbide, CaC2 and Silicon Tetrachloride (SiCl4). Al4C3 was synthesized from aluminium (Al) powder and graphite (C) powder by wet mixing method. Al4C3 was deposited on p-type Si wafer using carbon paste technique. The deposited Si wafer was reacted with flowing SiCl4 in quartz tube with combinations of 400 °C to 600 °C for 1 hour to 3 hours with gas flow rate from 100 cc/min to 300 cc/min. The effects of these parameters on the formation of SiC were characterized by X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy-Energy Dispersive X-ray (FESEM-EDX), Inductive Coupled Plasma-Optical Emission Spectroscopy (ICP-OES), and Fourier Transform Infrared Spectroscopy (FTIR). SiO2 peak at 70° in XRD which can be observed in design of experiment (DOE) at reaction rate of500° C, reaction time of 2 hours and gas flow rate of 200 cc/min , whereas Si-C bond stretching was observed at around 800cm-1 in all DOE runs, the maximum stretching Si-C in Run 7 (reaction rate: 600° C, reaction time: 3 hours, gas flow rate: 300 cc/min) with regards to FTIR data. FESEM-EDX showed elemental composition of Si, C, Al and O, suggested that oxidation happened altogether with chlorination process. Si presented ICP-OES has proved the carbothermal reduction process took place but the process was less reacted with SiCl4. Therefore, SiC not successfully formed, however, partially formation of SiC was observed in SEM/EDX analysis.